Ultrafiltration in Acute Heart Failure - Maria Rosa Costanzo (Radcliffe Medical Media, 2019)
Congestion is the predominant cause of more than 1 million annual heart failure hospitalisations and recurrent fluid overload predicts poor outcomes. Unresolved congestion trumps serum creatinine increases in predicting adverse heart failure outcomes. No pharmacological approach for acute heart failure has reduced these deleterious consequences. Simplified ultrafiltration devices permit fluid removal in lower acuity hospital settings, but results regarding safety and efficacy have been variable. However, adjustment of ultrafiltration rates to patients’ vital signs and renal function has been associated with more effective decongestion and fewer heart failure events. Many aspects of ultrafiltration, including patient selection, fluid removal rates, venous access, prevention of therapy- related complications and costs, require further investigation.